MOTIVASI DAN KEMANDIRIAN BELAJAR PADA MAHASISWA BARU - Daulay, Nurussakinah (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2021)
This study aims to determine learning independence which is influenced by the learning motivation of new students. A total of 460 new students of class 2019 were involved in this research. The instrument used was a scale of self-regulated learning and a scale of learning motivation. The data analysis used is the assumption test, hypothesis test, and difference test. The results show 1) based on the assumption test that the research data is proven normality and linearity; 2) based on the hypothesis test that there is a positive relationship between learning motivation and self-regulated learning (r = 0.770; p <0.01), and there is an effect of learning motivation on self-regulated learning (R² = 0.592; p <0.01); 3) based on different tests that there are differences in self-regulated learning based on student demographic factors [F = 1.321, p <0.05].Learning Motivation